2016
DOI: 10.1080/10286020.2016.1232253
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated isoflavones from Cudrania tricuspidata inhibit NO production in RAW 264.7 macrophages and suppress HL-60 cells proliferation

Abstract: Inhibitory effects of NO production in RAW 264.7 macrophages guided the isolation of nine prenylated isoflavones, including a new cudraisoflavone L (1) and eight known metabolites furowanin B (2), erysubin A (3), wighteone (4), lupalbigenin (5), laburnetin (6), isolupalbigenin (7), 6,8-diprenylorobol (8), millewanin H (9) from the leaves of Cudrania tricuspidata. At the concentration of 10 μM, compounds 1, 2, and 4 significantly inhibited NO production with the inhibitory values of 72.5 ± 2.4, 66.9 ± 1.8, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The 13 C NMR spectrum displayed a total of 22 carbon resonances, including two methyls, three sp 3 methylenes, five sp 2 methines, and 12 sp 2 quaternary carbons. These spectroscopic features were very similar to those of cudraisoflavone L, which was recently isolated from the same genus and shared the same molecular formula with 4 [26]. Their structural difference was only due to the location of the prenyl group and the hydroxyethyl moiety.…”
Section: Resultssupporting
confidence: 74%
“…The 13 C NMR spectrum displayed a total of 22 carbon resonances, including two methyls, three sp 3 methylenes, five sp 2 methines, and 12 sp 2 quaternary carbons. These spectroscopic features were very similar to those of cudraisoflavone L, which was recently isolated from the same genus and shared the same molecular formula with 4 [26]. Their structural difference was only due to the location of the prenyl group and the hydroxyethyl moiety.…”
Section: Resultssupporting
confidence: 74%
“… 2017 ; Tuan Anh et al. 2017 ). Our previous report showed that the compounds isolated from this plant display anti-neuroinflammatory effects (Yoon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Through this, a study was conducted to find out the effect of 6,8-diprenylorobol, which is one of the Cudrania tricuspidata extracts showing various effects. 6,8-Diprenylorobol belongs to the class of flavonoids and can be extracted from the leaves of Cudrania tricuspidata [ 13 ]. 6,8-Diprenylorobol exhibits anti-cell proliferation, anticancer, antifungal and anti-Helicobacter pylori activities [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%